HUBUNGAN STRES IBU DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI DI WILAYAH KERJA PUSKESMAS ALALAK SELATAN BANJARMASIN - Suparma, Fitri Septiyani; Rizkika, Delia Tri (Jurnal Delima Harapan, 2025)
Background: Exclusive breastfeeding is established as a strategy to accelerate stunting reduction, however, the existing coverage problem has not reached the target of 80% and the Alalak Selatan Community Health Center has been recorded as having a coverage of 75.2%. Maternal stress is suspected to be one of the triggers for low breast milk production so that exclusive breastfeeding cannot be given optimally, which can lead to stunting. Objective: To analyze the relationship between maternal stress and exclusive breastfeeding in infants in the Alalak Selatan Community Health Center working area. Method: This quantitative study used a cross-sectional correlative analytical design. The sample in this study was 35 mothers and infants aged 6-12 months who were selected by purposive sampling. Data collection used the Holmes-Rahe stress scale questionnaire and closed-ended questions about exclusive breastfeeding. Data were analyzed using the Kolmogorov Smirnov Z correlation test because the chi-square requirement was not met, this was indicated by the presence of 6 cells (75%) that had an estimated value <5. Results: The majority of respondents were identified as not experiencing stress with a total of 15 people (42.9%), not providing exclusive breastfeeding with a total of 18 people (51.4%), and having stunted babies with a total of 19 people (54.3%). The results of the study showed a p value = 0.000. Conclusion: based on the results of the research analysis that has been carried out, it is stated that there is a relationship between maternal stress and exclusive breastfeeding in infants in the work area of ​​the Alalak Selatan Community Health Center.